THE EFFECT OF RECRUITMENT, PLACEMENT, AND PERFORMANCE APPRAISAL ON EMPLOYEE PERFORMANCE AT TANTI KIRANA CLINIC RANGKASBITUNG - Tyara Frameswary; Franky; Zahera Mega Utama (BETRIK, 2024)
The title of this research is The Effect of Recruitment, Placement, and Performance Appraisal on Employee Performance at Tanti Kirana Clinic Rangkasbitung. Aims: 1) to find out, determine, and analyze the effect of recruitment on employee performance at Tanti Kirana Clinic Rangkasbitung 2) to find out, determine, and analyze the effect of placement on employee performance at Tanti Kirana Clinic Rangkasbitung 3) to find out, determine, and analyze the effect of performance appraisal on employee performance at Tanti Kirana Clinic Rangkasbitung 4) to find out, determine, and analyze the effect of recruitment, placement, and performance appraisal on employee performance at Tanti Kirana Clinic Rangkasbitung. Method: This research method is associated correlation with a quantitive approach. Sampling data in this research is simple random sampling. The population in this study was 160 employees at Tanti Kirana Clinic Rangkasbitung. The sample in this study was 62 respondents. Results: 1) Recruitment has a significant effect on employee performance at Tanti Kirana Clinic Rangkasbitung 2) Placement has a significant effect on employee performance at Tanti Kirana Clinic Rangkasbitung 3) Performance Appraisal has a significant effect on employee performance at Tanti Kirana Clinic Rangkasbitung 4) Recruitment, Placement, and Performance Appraisal have significant effect on employee performance at Tanti Kirana Clinic Rangkasbitung.